A complex pediatric cervical lymphadenopathy – Case Report - Kiaunytė, Saulė (AME Case Reports, 2026)
Background: Cervical lymphadenopathy associated with Mycoplasma pneumoniae is an uncommon manifestation. Nevertheless, it should be considered in the differential diagnosis of prolonged fever combined with other symptoms and not overlooked as a potential underlying cause.Case Description: This case report describes a five-year-old girl presenting with high-grade fever, cough, neck and throat pain, and enlarged cervical lymph nodes. At initial presentation, this case appeared relatively straightforward, with laboratory findings suggestive of a bacterial infection. Accordingly, a diagnosis of bacterial tonsillitis and lymphadenitis was established, and treatment with a broad-spectrum penicillin was initiated. The patient demonstrated initial signs of clinical improvement during the first two days of hospitalization; however, enlarged and painful lymph nodes persisted. By the end of the second hospital day, her condition deteriorated, with recurrence of high-grade fever. The challenging part of this case was the discrepancy between the clinical presentation and laboratory findings. Despite persistent fever and ongoing painful cervical lymphadenopathy, repeated laboratory investigations demonstrated improvement, including a decrease in leukocyte count, neutrophilia, and C-reactive protein levels. Following thorough evaluation and serial blood testing, elevated M. pneumoniae IgM levels were identified. After initiation of macrolide therapy, the patient achieved full clinical recovery.Conclusions: This case report highlights the importance of considering atypical bacterial infections in the differential diagnosis. Clinicians should be aware that these pathogens may present with atypical clinical manifestations, which can complicate and delay diagnosis.